2021
DOI: 10.1177/2472630320969147
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signatures in Pediatric Crohn’s Disease Patients with Mild or Quiescent Disease Treated with Partial Enteral Nutrition: A Feasibility Study

Abstract: Little is known about the metabolic response of pediatric Crohn’s disease (CD) patients to partial enteral nutrition (PEN) therapy and the impact of disease activity and inflammation. We analyzed plasma samples from a nonrandomized controlled intervention study investigating the effect of partial enteral nutrition (PEN) on bone health and growth throughout one year with untargeted metabolomics using high-performance liquid chromatography (HPLC) coupled with high-resolution mass spectrometry (HRMS). Thirty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 64 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Intestinal symbiotic bacteria can inhibit the growth of pathogenic bacteria and maintain intestinal homeostasis [ 13 ]. Short-chain fatty acid (SCFA) represents metabolites produced by the intestinal flora and might occupy an important position in the occurrence and development of CD [ 14 16 ]. According to Ceylan Tanes et al [ 17 ], EEN or other special dietary might change the structure of specific metabolites by affecting the microbiome of healthy volunteers, thus affecting the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal symbiotic bacteria can inhibit the growth of pathogenic bacteria and maintain intestinal homeostasis [ 13 ]. Short-chain fatty acid (SCFA) represents metabolites produced by the intestinal flora and might occupy an important position in the occurrence and development of CD [ 14 16 ]. According to Ceylan Tanes et al [ 17 ], EEN or other special dietary might change the structure of specific metabolites by affecting the microbiome of healthy volunteers, thus affecting the inflammatory process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the flavonoids identified in this study should be from the food of horses. It has been reported that fatty acids and isoprenoids can be involved in many physiological and immune processes ( 53 , 54 ). Isoflavonoids possess a wide range of pharmacological properties, such as antibacterial function ( 55 ), which can alter the symbiosis relationship among microbes.…”
Section: Resultsmentioning
confidence: 99%
“…Incidentally, only two of them are known metabolites: Asp Phe Ser Leu and withaperuvin E. The function of the short peptide is unknown. Withaperuvin E, a plant-derived C28 steroidal lactone [ 46 ] belonging to a family of compounds with potential anti-inflammatory activity, is mediated by the inhibition of the tumor necrosis factor alpha (TNF-α)-induced nuclear factor kappa B (NF-κB) activity [ 47 , 48 ]. Our findings suggest the existence of the synthetic gene cluster of withaperuvin E in S. albulus CICC11022, and the synthesis of this substance has a certain coupling relationship with Pls.…”
Section: Discussionmentioning
confidence: 99%